TAX OPTIMIZATION AND TAX EVASION IN UKRAINE - Разумова, Анна; Протопопова, Наталья; Джанумова, Лидия (SWorldJournal, 2020)
Abstract. Introduction. The article clarifies the content and connection of the categories "data optimization" and "tax evasion". Illegal and legal ways to reduce the tax burden, ways to achieve the planned level of the final financial result in the iden